Antioxidant Activity Test of Cinnamon Root Extract Cinnamomum burmanii (Nees & T.Nees) Blume) Based on Solvent Polarity Level - Sri Wahyuni, Riza; Arel, Afdhil; Widya, Nurul (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2024)
Antioxidants are chemical compounds that can donate one or more electrons to free radicals to inhibit free radical reactions. One part of the plant that has the potential to act as an antioxidant is cinnamon root (Cinnamomum burmanii (Nees T.Nees) Blume). The aim of this research was to determine the antioxidant activity of cinnamon root based on solvent polarity. Antioxidant activity testing was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method and using vitamin C as a comparison solution. Antioxidant activity is expressed in the form of IC50. The results obtained from the maximum absorption wavelength of DPPH are 517 nm, with an absorbance of 0,717. The results of comparative antioxidant activity for vitamin C obtained IC50= 3,51 µg/mL, and samples of cinnamon root extract with IC50 values= 406 µg/mL for n-hexane extract, 53,2 µg/mL for ethyl acetate extract and 78,9 µg/mL for 70% ethanol extract. Based on the research results obtained, the antioxidant activity of the 70% ethanol and ethyl acetate cinnamon root extract samples is classified as strong (50- 100 µg/mL) while the n-hexane cinnamon root extract